2019
DOI: 10.56454/scjm9847
|View full text |Cite
|
Sign up to set email alerts
|

Cotton (Gossypium hirsutum L.) Injury, Growth, and Yield Following Low-Dose Flumioxazin Postemergence Applications

Abstract: The effects of postemergence (POST) herbicides off-target movement on cotton has been evaluated, but no data is available evaluating simulated off-target movement of residual herbicides. Therefore, low-dose POST applications of flumioxazin were evaluated in cotton at the cotyledon, two- and four-leaf growth stages. Rates evaluated were 12.5, 25, and 50% of the labeled use rate of 72 g ai ha-1. Necrosis, cotton height and width reduction was observed. Cotyledon cotton was injured 69 to 86%, 80 to 91%, and 84 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, our findings are in agreement with those of Young et al (2003), who reported that soybean injury decreased as soybean growth stage increased following mesotrione postemergence. Similarly, soybean and cotton injury following low-dose flumioxazin decreased as growth stage increased (Stephenson et al 2019a(Stephenson et al , 2019b.…”
Section: Isoxaflutole Studymentioning
confidence: 94%
See 3 more Smart Citations
“…However, our findings are in agreement with those of Young et al (2003), who reported that soybean injury decreased as soybean growth stage increased following mesotrione postemergence. Similarly, soybean and cotton injury following low-dose flumioxazin decreased as growth stage increased (Stephenson et al 2019a(Stephenson et al , 2019b.…”
Section: Isoxaflutole Studymentioning
confidence: 94%
“…At all locations, treatments were applied with a CO 2 -pressurized backpack sprayer in a constant carrier volume of 140 L ha −1 . Others have simulated off-target movement of herbicides utilizing constant carrier volume (Al-Khatib et al 2003;Bailey and Kapusta 1993;Ellis et al 2003;Sperry et al 2019;Stephenson et al 2019aStephenson et al , 2019bSteppig et al 2018). At Alexandria, all treatments were applied at 190 kPa using four flat-fan 11002 nozzles (AIXR TeeJet®, TeeJet Technologies Southeast, P.O.…”
Section: Concurrentmentioning
confidence: 99%
See 2 more Smart Citations